Perception of Arable Crop Farmers on Child Labour in Sagamu Local Government Area, Ogun State, Nigeria - Mufutau, Rafiu Adeniyi; Oladoja, M.A.; Adeokun, O.A.; Osunmakinde, E. O.; Nwaorgu, D.P. (Acta Universitatis Danubius. Œconomica, 2022)
The study focused on perception of child labour among arable crop farmers in Sagamu Local Government, Ogun State, Nigeria. Questionnaire was used to collect data from 132 arable crop farmers on socio-economic characteristics, reasons for engaging children in arable crop farming, factors influencing child labour and perception of child labour. Data was analysed using descriptive statistical tools and inferential tools such as Chi-square and Pearson Product Moment Correlation at p≤0.05 level of significance. Results indicate that arable crop farmers were within age category of 38-47 years and majority were married (88.6%), males (60.0%) who were well educated (94.7%) and were primarily traders (72.0%). Very few (39.4%) had access to credit facilities but operated on an average land-space of 5 acres, earning between ₦50,001-₦100,000 annually. There was unfavourable perception of child labour among majority (65.2%) of arable crop farmers in the study area while consequences of child labour were general child injuries (2.18). Test of hypotheses shows significant relationship between perception of child labour and secondary occupation (9.716), labour used (9.997), contact with extension workers (11.448), transmission of farming skills and knowledge (-0.250), training children to be independent (0.204), high cost of labour (.409), high cost of living (.531), low income (.363), lack of political will to empower farmers (0.258), and ignorance of policies of child labour (.408). In conclusion, arable crop farmers had unfavourable perception of child labour in the study area. The study therefore recommends more awareness on negative impact of child labour, organizing seminars, training and financial assistance to child guardians and parents to ameliorate severity of child labour consequences.